Interferon-γ Stimulates Monocyte Chemotactic Protein-1 Expression by Monocytes - J. M. Liebler; S. L. Kunkel; R. M. Allen; M. D. Burdick; R. M. Strieter (Hindawi Limited, 1994)
Monocyte chemotactic protein (MCP-1) is a specific monocyte chemoattractant and activating factor produced by both immune cells (mononuclear phagocytes and lymphocytes) and non-immune cells (parenchymal and stromal cells). In order to define the conditions under which human monocytes express MCP-1, monocytes were exposed to IFN-γ, IL- lβ, TNF-α, IL-4 or PHA under serum free conditions. There was no significant MCP-1 production by monocytes following exposure to IL-lβ, TNF-α or IL-4. In contrast, stimulation with IFN-γ resulted in a dose dependent increase in MCP-1 protein and mRNA expression. Simultaneous stimulation with IFN-γ and IL-1β or TNF-α resulted in no further increase in MCP-1 production. It is concluded that IFN-γ, primarily a product of TH1 T lymphocytes, stimulates the expression of MCP-1 by monocytes.